Winnipeg's Palliser Furniture in the Context of Mennonite Views on Industrial Relations, 1974-1996 - Thiessen, Janis Lee (Prairie Metropolis: New Essays on Winnipeg Social History, 2009)
Discusses the evolution of the Mennonite approach to labour relations in Manitoba with reference to an unsuccessful unionization drive at Palliser Furniture in Winnipeg in the 1990s.
Keywords: 19th century; History; Manitoba; Social conditions; Social institutions; Winnipeg; Winnipeg (Man.)